Pengaruh Konsentrasi Penambahan Bubuk Kunyit (Curcuma domestica Val.) sebagai Pengampelas dan Antioksidan terhadap Karakteristik Krim Body Scrub - Megayanti SJ, Ni Kadek; Wrasiati, Luh Putu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 9 No 4 (2021): Desember, 2021)
This study aims to determine the effect of the concentration of turmeric powder (Curcuma domestica Val.) as an abrasive and an antioxidant on the characteristics of a body scrub cream and to determine the concentration of adding turmeric powder (Curcuma domestica Val.) as an abrasive and an antioxidant to produce the best characteristics of body scrub cream. This study used a randomized block design with variations in the concentration of turmeric powder with six concentration (0%, 2%, 4%, 6%, 8%, and 10%). The treatments were grouped into 3 based on the time of making body scrub cream so that 18 experimental units were obtained. Data were analyzed by analysis of variance and continued with Tukey's test. The concentration treatment of adding turmeric powder greatly affects pH, viscosity, spreadability, adhesion, total phenol, and overall organoleptic acceptance. The concentration of adding turmeric powder 4% is the best treatment to produce a body scrub cream with the following characteristics: pH 6.52, viscosity 26.933.33 cp, spreadability 5.15 cm, adhesion 9.71 seconds, total phenol 3.19 mgGAE /g, separator ratio= 1, and overall organoleptic acceptance of 6.40 (like to like very much).  Keywords : Body scrub cream, Curcuma domestica Val. , Antioxidant, Sandpaper